MEASURING THE AWARENESS OF AUSTRALIAN MUSLIMS TOWARDS SHARI'AH COMPLIANT BANKING PRODUCTS. - Hussain G. Rammal; Ralf Zurbruegg (Indonesian Management and Accounting Research, 2013)
This paper seeks to find out the demand for Islamic finance among the Muslim community in Australia. A survey was conducted in Adelaide during the first half of 2004 covering Muslims attending Friday prayers. Of the respondents, 58.3 percent stated that they were aware of Islamic financing. With the Australian Muslim community growing in number, the results of this survey represent opportunities for Australian financial institutions to provide financing to Muslims who previously have stayed away from conventional interestbearing loans. Keywords: Australian Muslims, Islamic Finance.